The Effect of B-Adrenergic Agonist Injection and Feeding Energy Level on Blood Plasma Non-Esterified Fatty Acids in The Lactating Dairy Ewe - Ali Agus; Francois Bocquier; Anne Ferlay; Yves Chilliard (Buletin Peternakan, 2002)
Artikel dalam bentuk PDF